Effects of ball kicking dual task training on gait performance and balance in individuals with chronic hemiparetic stroke - Kim, Minseong; Shim, Jaehun; Yu, Kyunghoon; Kim, Jiwon (Physical therapy rehabilitation science, 2016)
Objective: The purpose of this study was to compare the effect of ball kicking dual task gait training with the addition of a cognitive task with general treadmill gait training (TGT) on gait speed, gait endurance, functional gait, balance and balance confidence in patients with chronic hemiparetic stroke. Design: Randomized controlled trial. Methods: Fourteen stroke patients who volunteered to participate in this study were randomly divided into two groups with seven patients in each group: ball kicking dual task training (DTT) group and TGT group. The DTT group received ball kicking DTT with cognitive tasks consisted of three stages and the TGT group received TGT using normal walking speed, respectively, for 30 minutes per day 3 days per week for 4 weeks. Outcome assessments were made with the 10-meter walking test (10MWT), 6-minute walking test (6MWT), functional gait assessment (FGA), Berg balance scale (BBS), timed up and go test (TUG), and the activities-specific balance confidence (ABC) scale. Results: The DTT group showed more significant improvement in the 10MWT, 6MWT, FGA, BBS, TUG, and ABC than the TGT group (p<0.05). In addition, within groups comparison showed significant improvement in all variables (p<0.05). Conclusions: The findings suggest that both ball kicking dual task gait training and TGT improve gait performance and balance in patients with chronic hemiparetic stroke. However, ball kicking dual task gait training results showed more favorable outcomes than TGT for chronic hemiparetic stoke patients. KCI Citation Count: 0